Accumulation and evolution of ice jams influenced by different ice discharge: An experimental analysis - Chen, Pangpang; Cheng, Tiejie; Wang, Jun; Cao, Guangxue (Frontiers in Earth Science, 2023)
Ice jam, a unique hydrological phenomenon of rivers in cold regions, is a major cause of ice flooding. There are many different kinds of damage that can result from ice jams: e.g., blockage of the water flow, rising water levels that can flood farmland and dwellings, damage to hydraulic structures, and interruptions to shipping. The formation of an ice jam is influenced by various factors associated with different fields of study. The accumulation of an ice jam is thus a complex process worth investigating. However, previous studies seldom take account of ice discharge factors. This study carries out 29 tests on the accumulation of an ice jam, and discovers four kinds of phenomena: inlet ice that fails to submerge (case 1); thickening ice from upstream to downstream (case 2); thickening ice from downstream to upstream (case 3); and failure to form an ice jam (case 4). Two typical examples are used to detail cases 2 and 3. The authors suggest differentiating between the two cases using the longitudinal boundary line running through the point of the Froude number (Fr) = 0.119. Furthermore, the authors analyze the phenomena that make it difficult for an ice jam to form and suggest using the critical discriminant line to distinguish between cases 3 and 4. Combined with the longitudinal boundary line, a partition result diagram of the different accumulation features of ice jams is presented to differentiate between the four modes of accumulation of ice jams.